Simbol Diskursif dan Presentasional Sintren - Putra, Agung Trihandono (PANTUN: Jurnal Ilmiah Seni Budaya, 2019)
Sintren was born and developed in the coastal areas of the island of Java, precisely in the Cirebon area. Sintren is unique and sacred in which makes the dancers feel the trance (angelic trance). This study analyzes the meaning of the symbols applying the symbol theory. Susanne Langer divides art symbols into two categories, discursive and presentational symbol theory. Discursively, sintren has several sequential stages. First, sintren is tied. Then she is put into a cage, exiting from the cage while clothes have been changed. Getting out from the cage, the dancers are already in their full costume including the glasses. The final phase is the dancer to be awaken from the trance conditions. Meanwhile for presentation symbol, it is initially as cleaning village ritual for the safety and blessing in the village. This ritual is to pray for the village to be protected from catastrophe or unwanted calamities. Keywords: Art, dance, sintren, trance, symbol